ANALISIS OPINI PUBLIK TERHADAP REPUTASI MEREK - Lelli Kisdayanti; Nur Farida (Bajang Institute, 2026)
Brand reputation is a strategic asset that plays a crucial role in determining a company’s sustainability and competitiveness in an increasingly dynamic business environment. In the digital era, public opinion develops rapidly through various media channels, particularly social media, and has a significant influence on the formation of brand image and reputation. This article aims to analyze the influence of public opinion on brand reputation and to identify the factors that shape public perceptions of a brand. This study employs a qualitative approach with a descriptive method, utilizing literature review and document analysis of academic articles, media reports, and relevant digital content. The findings indicate that public opinion is shaped by media exposure, consumer experiences, social environments, and viral issues on social media. Positive public opinion contributes to strengthening brand reputation, consumer trust, and loyalty, while negative public opinion can damage brand image and trigger reputational crises. Therefore, companies are required to manage public opinion strategically through effective communication, consistent product and service quality, and continuous social media monitoring to maintain and enhance brand reputation.